Temporal Lobe Cavernous Malformation Caused Epileptic Amnesic Episodes and Mild Cognitive Impairment - Hirokawa, Yusuke; Fujimoto, Ayataka; Ichikawa, Naoki; Sato, Keishiro; Tanaka, Tokutaro; Enoki, Hideo; Otsuki, Yoshiro; Okanishi, Tohru (Frontiers in Neurology, 2019)
Neuropathological features in Alzheimer’s disease (AD) are amyloid β (Aβ) deposits and neurofibrillary changes. AD is characterized by memory impairment and cognitive dysfunction, with some reports associating these impairments with hyperexcitability caused by Aβ in the medial temporal lobe. Epileptic seizures are known to be common in AD. We encountered a 65-year-old patient with cavernous malformation (CM) in the right temporal lobe who exhibited epileptic amnesia (EA) and AD-like symptoms. Scalp electroencephalography (EEG), including long-term video-EEG, showed no interictal discharges, but intraoperative subdural electrode recording from the right parahippocampal area showed frequent epileptiform discharges. Neuropathologically, senile plaques were found in the surrounding normal cortex of the CM. Postoperatively, the patient has remained free of EA and AD-like symptoms since total removal of the CM. This is the first surgical case report to confirm temporal lobe hyperexcitability associated with EA and AD-like symptoms.